Magnolol attenuates neointima formation by inducing cell cycle arrest via inhibition of ERK1/2 and NF-κB activation in vascular smooth muscle cells - Karki, Rajendra; Ho, Oak-Min; Kim, Dong-Wook (Biochimica et biophysica acta. General subjects, 2013)
Endovascular injury induces switching of contractile phenotype of vascular smooth muscle cells (VSMCs) to synthetic phenotype, thereby causing proliferation of VSMCs leading to intimal thickening. The purpose of this study was to assess the effect of magnolol on the proliferation of VSMCs in vitro and neointima formation in vivo, as well as the related cell signaling mechanisms. Tumor necrosis factor alpha (TNF-α) induced proliferation of VSMCs was assessed using colorimetric assay. Cell cycle progression and mRNA expression of cell cycle associated molecules were determined by flow cytometry and reverse transcription polymerase chain reaction (RT-PCR) respectively. The signaling molecules such as ERK1/2, JNK, P38 and NF-κB were determined by Western blot analysis. In addition, rat carotid artery balloon injury model was performed to assess the effect of magnolol on neointima formation in vivo. Oral administration of magnolol significantly inhibited intimal area and intimal/medial ratio (I/M). Our in vitro assays revealed magnolol dose dependently induced cell cycle arrest at G0/G1. Also, magnolol inhibited mRNA and protein expression of cyclin D1, cyclin E, CDK4 and CDK2 in vitro and in vivo. The cell cycle arrest was associated with inhibition of ERK1/2 phosphorylation and NF-κB translocation. Magnolol suppressed proliferation of VSMCs in vitro and attenuated neointima formation in vivo by inducing cell cycle arrest at G0/G1 through modulation of cyclin D1, cyclin E, CDK4 and CDK2 expression. Thus, the results suggest that magnolol could be a potential therapeutic candidate for the prevention of restenosis and atherosclerosis. [Display omitted] ► Magnolol was isolated from Magnoliae Cortex using column chromatography. ► Magnolol inhibited neo-intima formation in vivo. ► Magnolol induced cell cycle arrest at G0/G1 phase. ► Proliferation of VSMCs was ERK1/2 and NF-κB dependent.